Drug Education Information Services with a Humanistics Approach in Preventing Narcotics Use in PIK R Asam Kumbang Organization - Salbiah Salbiah; Sri Ngayoumi Yudha Wastuti (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the implementation of information services with a humanistic approach in socializing education about drug abuse (Narcotics, Alcohol, Psychotropics, and Other Addictive Substances) at PIK-R (Adolescent Counseling Information Center) Asam Kumbang. The research method used is a qualitative descriptive approach using the Miles and Huberman Model. Data was collected through observation, interviews, and documentation. The results showed that although PIK-R has been active in providing information and counseling on reproductive health and adolescent problems, socialization about the dangers of drug abuse is still lacking in the Asam Kumbang environment. Further efforts are needed to improve such socialization, with a humanistic approach that emphasizes empathy, unconditional acceptance, and strengthening individual potential. The implementation of NAPZA Education at PIK-R Asam Beetle is expected to help adolescents understand the dangers of narcotics and prevent their misuse in their environment.